PENGEMBANGAN PROFESIONALITAS PUSTAKAWAN KEPENDIDIKAN PERPUSTAKAAN IAI NGAWI - Sadiran (Institut Agama Islam Ngawi, 2022)
Abstract History proves that libraries in the Islamic world gave birth to Islamic geniuses, especially in the first phase of the Abbasid Dynasty led by Caliph Abu Ja; far al Mansyur, Caliph Harun al Rashid, and Abdullah al Makmun, were caliphs who carefully guarded and preserved good books. which have religious and general nuances, both the work of Muslim and non -Muslim scientists, both the work of contemporary scientists and their predecessors. IAI Ngawi Library is quite advanced and complete, proven to have Library Staff alumni UIN Sunan Kalijaga Library Management Program, of course able to manage and serve students and lecturers when they want to use the library facilities, open every working hour from 13.30 to 17.00; Library activities in addition to services also hold training on DDC classification codes, the coordinate code has been adjusted to the library. Librarians are able to maintain and manage books as the main driver in order to increase academic intelligence and cultivate a culture of love of reading through motivation and adequate library building facilities. Keywords: Library, Development and Professionalism of Educational Librarians.